IN LIGHT OF ‘NKANDLA’, WHAT IS THE ROLE OF THE PUBLIC PROTECTOR IN UPHOLDING THE RULE OF LAW IN SOUTH AFRICA? (The Pretoria Student Law Review, 2021)
The focus of this article will be to ascertain what role, if any, the Public Protector plays in achieving and upholding the rule of law as envisaged in section 1(c) of the Constitution. In doing so, I will assess the powers of the Public Protector as envisaged by the Constitution and supporting legislation and analyse the effect of recommendations made by the Public Protector. I will then offer a discussion on certain shortfalls within the legislation that have become a hindrance to the Public Protector achieving her mandate in practice. I will, further, highlight the importance of the powers of the Public Protector as an avenue to achieving the rule of law, and, offer an analysis of the judgments in South African Broadcasting Commission v Democratic Alliance and Economic Freedom Fighters v Speaker of the National Assembly. I will, finally, conclude by discussing possible solutions to the challenges faced by the Public Protector in practice and offer a summary of my views.
Keywords: Public Protector; upholding the rule of law; section 1(c) of the Constitution; South African Broadcasting Commission v Democratic Alliance; Economic Freedom Fighters v Speaker of the National Assembly; powers of the Public Protector